The Relationship between Creative Accounting Risks and Auditing Risks from the Perspective of External Auditors in Saudi Arabia - Ghamri, Wejdan Hassan M (Financial Risk and Management Reviews, 2020)
The present study aimed to identify the relationship between creative accounting risks and auditing risks from the perspective of external auditors in Saudi Arabia. The sample comprised licensed auditors who serve in Saudi statutory audit offices. The outcomes showed that external auditors were aware of creative accounting risks. In addition, their professional technical factors, such as professionalism, commitment to training programs and continuing education, mentorship, considering professional standards in auditing, good planning for external auditing, their supervision of auditing teamwork, and auditing fees, enormously helped identify creative auditing practices. There were no statistically significant differences in the external auditors’ estimates of the effect of creative accounting risk on auditing risks according to the variables of (academic qualification, professional qualification, occupation, and experience). No statistically significant differences were found in the external auditors’ estimates of the external auditor’s responsibility to detect creative accounting practices according to these variables. The research recommends giving concern to the concept of creative accounting risks, and set the standards and procedures that the auditor must follow to address these practices because of their negative effects on the reliability of the financial statements.